2017
DOI: 10.1111/1471-0307.12383
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme‐inhibitory activity and antimicrobial effect of fermented camel milk (Camelus dromedarius)

Abstract: This study aimed to determine the angiotensin converting enzyme-inhibitory activity and antimicrobial effect of fermented camel milk. Samples were prepared either using Lactobacillus acidophilus and Streptococcus thermophilus or Lactobacillus helveticus and Str. thermophilus and labelled as S1 and S2, respectively. The IC 50 values of S1 and S2 samples ranged between 113-200 and 70-133 lg/mL, respectively. The antimicrobial effects of S1 and S2 samples against Bacillus cereus, Salmonella Typhimurium and Staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…rhamnosus. The ACE inhibitions of camel milk fermented by Lc.K782 were greater than those reported by Alhaj et al (2017), who fermented camel milk by Lb. acidophilus and Streptococcus thermophiles or Lactobacillus helveticus.…”
Section: Ace-inhibition Activitycontrasting
confidence: 64%
See 1 more Smart Citation
“…rhamnosus. The ACE inhibitions of camel milk fermented by Lc.K782 were greater than those reported by Alhaj et al (2017), who fermented camel milk by Lb. acidophilus and Streptococcus thermophiles or Lactobacillus helveticus.…”
Section: Ace-inhibition Activitycontrasting
confidence: 64%
“…Australia has half a million wild camels, especially in the Northern Territory. Worldwide, there are 2 wellknown species of camels: 1-humped Arabian camels or dromedaries (Camelus dromedarius; the camels of the plains) and 2-humped Bactrian camels (Camelus bac-901 2013; Alhaj et al, 2017). Few attempts have been made to compare the health-promoting benefits of fermented camel milk with the benefits of other fermented mammalian milks, particularly fermented bovine milk (Mymensingh, 2007;Moslehishad et al, 2013;Shori, 2013), with an emphasis on ACE inhibition, antioxidant, and proteolytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Unhydrolyzed CWP showed ACE-IA, which could be due to the presence of some bioactive peptides liberated by the bacterial contamination of the raw camel milk or by the endogenous proteolytic enzymes [ 22 ]. Similarly, Alhaj et al [ 23 ] and Jafar et al [ 24 ] reported ACE-IA for the untreated camel milk and the unhydrolyzed CWP. The hydrolysis of the CWP with papain significantly ( p ˂ 0.05) enhanced its ACE-IA as a result of the augmented release of multiple bioactive peptides with ACE-IA.…”
Section: Resultsmentioning
confidence: 87%
“…Bioactive peptides derived from Lactobacillus acidophilus and Streptococcus thermophilus fermented camel milk showed ACE inhibitory and antimicrobial activities against Bacillus cereus, Salmonella Typhimurium, and Staphylococcus aureus. Bioactivities were time and strain-dependent wherein microbial inhibition activity was observed after 12 h of incubation till 15 days (Alhaj et al 2018). Camel milk fermented by Leuconostoc lactis, isolated from traditional fermented camel milk (Chal),had antioxidant activity as revealed by significantly higher ABTS and DPPH activity (Soleymanzadeh et al 2016).…”
Section: Fermented Milk (Yoghurt)mentioning
confidence: 99%